Performance of two egg parasitoids of brown marmorated stink bug before and after cold storage - Li, Wen-Jing; Chen, Ju-Hong; Avila, Gonzalo A.; Ali, Muhammad-Yasir; Tian, Xin-Yue; Luo, Zheng-Yu; Zhang, Feng; Shi, Shu-Sen; Zhang, Jin-Ping (Frontiers in Physiology, 2023)
The genus Trissolcus includes a number of egg parasitoids that are known to contribute to control Halyomorpha halys. The number of progenies, particularly females, is important for efficient mass rearing of species used in augmentative during biological control programs. Cold storage is an important technique for extending the shelf life of nature enemies used in such programs. We assessed how fecundity, sex ratio, lifespan and number of hosts parasitized within 24 hours were affected by host density for T. japonicus and T. cultratus when offered fresh H. halys eggs, and how these parameters were affected if adult parasitoids were first held in cold storage (11°C in the dark) for 19 weeks before being used for propagation. The fecundity were 110.2 and 84.2 offspring emerged at 25°C, parasitoids not held in cold storage; among the offspring that emerged 82.6% and 85.6% were female for T. japonicus and T. cultratus, respectively. If first held in cold storage, T. japonicus and T. cultratus produced 35.1 and 24.6 emerged offspring per female, respectively, although cold storage significantly extended the shelf life. The survival rates of parasitoids that were held in cold storage was 90.3 and 81.3% for females, and 3.2 and 0.9% for males of T. japonicus and T. cultratus, respectively. The number of hosts parasitized within 24 hours was not shown density dependent, but it was significantly lower after cold storage. This information can be used to estimate the likely produced during augment rearing colonies for use in biological control programs.